PEMULIHAN AIR TANAH BERDASARKAN KAJIAN HIDROGEOLOGI DI CEKUNGAN AIR TANAH BANDUNG - SOREANG - Harnandi, Dadi (JURNAL SUMBER DAYA AIR, 2018)
The rapid development of many sectors at the Bandung-Soreang Groundwater Basin has increased the demand for clean water. It is estimated that approximately 70 per cent of the clean water demand is still fulfilled by ground water. In the last five years, the use of ground water from deep and dug wells has shown a tendency of increase. In 2001, total use of groundwater reached 46.6 million cu m, and in 2005 had increased to 51.4 million cu m. The increasing use of ground water at middle aquifer and deep aquifer has intensified the depth of ground water level. A distribution of ground water level decrease at middle aquifer was observed at some areas in West Java, i.e. South Cimahi – 91.0 m bgl; Dayeuhkolot – 62.0 m bgl; Rancaekek – Cimanggung – 68.0 m bgl; Majalaya – 43.0 m bgl; and the city of Bandung – 62.9 m bgl. The depth of ground water at deep aquifers at areas such as, South Cimahi, Dayeuhkolot, Cikeruh and Rancaekek varied between 24.7 - 68.2 m bgl. Between the years of 2000 and 2006, at middle- and deep aquifer respectively, the decrease of ground water level showed a rate of 0.11 – 12.03 m/year and 0.16 – 2.61 m/year.